The Influence of Surface Treatment with Zircos–E etching solution and Sandblast on The Surface Roughness of Zirconia (An in Vitro Study) (Mustansiria Dental Journal, 2024)
Purpose: To evaluate the effect of Zircos–E etching solution and sandblasting with Al2O 3particle on the roughness of zirconia ceramic. Material and methods: 45 monolithic zirconia discs (Vita YZ HT) with measurements of 2 millimeters in height and 10 millimeters in diameter were produced. All samples were machined, sintered, and the surface of each disc was smoothed using 600, 800, and 1200 grit aluminum oxide paper. Three groups were created based on the surface treatment applied to the discs, group (A): no treatment (control), group (B): sandblasting, and group (C) Zircos-E solution. Using a profilometer, the zirconia's surface roughness has been investigated for each group. The scanning electron microscope (SEM) has been utilized to analyse the morphological alterations of a specimen from every group. One-way ANOVA and Tukey HSD tests have been utilized to assess the data at the 5% significance level.Results: The zirconia surface roughness value was significantly increased by sandblasting with 50µm AL2O3 (1.921 µm). The zirconia surface roughness value did not significantly change after chemical treatment with Zircos-E etching solution (0.910 µm), as compared to the control group (0.601 µm). Conclusion: Acid etching has little impact on zirconia surface roughness, whereas zirconia surface roughness increases after AL2O3 sandblasting.